Neoliberal Pedagogies of Motherhood at an Ontario Early Years Centre - Pozniak, Kinga (Journal of the Motherhood Initiative for Research and Community Involvement, 2017)
This article examines how the neoliberal turn is shaping the realm of motherhood in Canada by focusing on the activities of government-funded Ontario Early Years Centres (OEYCs). New mothers are often targets for expert interventions that aim to fulfill particular political, economic, or social objectives. In the province of Ontario, many state-sanctioned messages about raising children are disseminated through OEYCs. I argue that OEYC activities are shaped by, and in turn reproduce, neoliberal values, techniques, and philosophies. Through their activities, OEYCs promote the values of responsibility, reliance on experts, risk management, and a commitment to self-improvement, thus inculcating in the participant mothers a subjectivity that is consistent with neoliberal objectives. This secures the optimal social reproduction of the future generation for the knowledge economy, while placing the entire responsibility for this on the shoulders of mothers. The case of the OEYCs illustrates the way in which the contemporary Canadian state acts on the most intimate areas of life to forge subjectivities that align people with neoliberal agendas.